Recent Trends in Surface Treatment Technologies for Airframe Adhesive Bonding Processing: A Review (1995-2008) - Park, Sang Yoon; Choi, Won Jong; Choi, Heung Soap; Kwon, Hyuk; Kim, Sang Hwan (The Journal of adhesion, 2010)
Proper surface treatment technologies are prerequisite for achieving long-term service capability through the adhesive bonding process. However, the current surface treatment technologies used in the adhesive bonding process for aluminum alloys depend on materials that are undesirable from an environmental- or safety perspective. Suitable alternatives in the aerospace industry are the subject of much interest: non-chromate anodizing, silane, sol-gel, laser, plasma, and ion beam enhanced deposition of Al 2 O 3 film. These approaches can eliminate, or greatly reduce, the undesirable hazardous materials and have been proven to deliver comparable bonding performance. In some cases these alternative processes may even outperform established processes, such as chromic and phosphoric acid anodizing.